Recent Advances in the Treattnent of Non-obstructive Urinary Tract Infection in Infants and Children - Friedrich Manz; Otto Mehls (Paediatrica Indonesiana, 1982)
In infants and children urinary tract infections are common and reccurent. For the first urinary tract infection elimination of bacteriuria with chemotherapeutic drugs is usually simple and effective. The long-term treatment of patients with urinary tract infection should reflect the individual risk to develop renal damage. Therefore, individual therapy must be picked out of several therapeutic schedules. Observation without chemotherapy, chemotherapy of active urinary tract infection, chemotherapeutic prophylaxis, suppressive chemotherapy, and surgery.